Ceramic/polymer microlattices: Increasing specific energy absorption through sandwich construction. (May 2022) - Diamantopoulou, Marianna; Roth, Christian C.; Tancogne-Dejean, Thomas; Lauener, Carmen M.; Mohr, Dirk
Abstract: The triply periodic minimal surface design (TPMS, Schwarz Primitive) is utilized to numerically investigate lattices with sandwich cell walls of constant macroscopic density. The sandwich construction of the cell walls involves a polymer (core material) and a ceramic material (skin). The ceramic (alumina) weight fraction in the sandwich construction is varied such that for each density a range of weight fractions from 0%wt (monolithic polymer) to 100%wt (monolithic alumina lattice) is under investigation in terms of the Young's modulus, peak stress and specific energy absorption. It is found that the specific energy absorption of sandwich TPMS lattices is higher compared to monolithic polymer or alumina TPMS lattices of equal density (42 kg m −3 ) with the 40%wt alumina lattice providing the highest specific energy absorption. At higher densities, the optimal energy absorption is obtained for 10% and 80%wt alumina lattices. Selected lattices of 10%, 30% and 40%wt alumina are fabricated via two-photon lithography and atomic layer deposition and are tested in situ under uniaxial compression. Utilizing the results of this study, design maps are constructed to provide guidelines fulfilling application-related requirements.